NF-KappaB in Long-Term Memory and Structural Plasticity in the Adult Mammalian Brain - Kaltschmidt, Barbara; Kaltschmidt, Christian (Frontiers in Molecular Neuroscience, 2015)
The transcription factor nuclear factor kappaB (NF-κB) is a well known regulator of inflammation, stress and immune responses as well as cell survival. In the nervous system NF-κB is one of the crucial components in the molecular switch, that converts short- to long-term memory, a process requiring de novo gene expression. Here, we will review published research on NF-κB and downstream target genes in mammals, which are necessary for structural plasticity and long-term memory, both under normal and pathological conditions in the brain. Genetic evidence has revealed that NF-κB does regulate neuroprotection, neuronal transmission and long-term memory. Additionally, after genetic ablation of all NF-κB subunits, a severe defect in hippocampal adult neurogenesis was observed during aging. Proliferation of neural precursors is increased, however axon outgrowth, synaptogenesis and tissue homeostasis of the dentate gyrus is hampered. In this process, the NF-κB target gene PKAcat and other downstream target genes such as Igf2 are critically involved. Thus, NF-κB activity seems to be crucial in regulating structural plasticity and replenishment of granule cells within the hippocampus throughout life. In addition to the function of NF-κB in neurons we will discuss data on a neuro-inflammatory role of the transcription factor in glia. Finally a model for NF-κB homeostasis on the molecular level is presented, in order to explain seemingly contradictory the friend or foe role of NF-κB in the nervous system.